Impact assessment confirms Participatory Rangeland Management's positive impact on rangelands and pastoral communities - Carleton, Elliot (International Livestock Research Institute, 2022)
In November and December 2021, the ILRI-led Livestock CRP contracted African Research and Economic Development Consultants to conduct an independent impact assessment of the Participatory Rangeland Management (PRM) pilot in Kenya and Tanzania. PRM works through three stages and eight steps, building the capacity of local communities to better manage their land in the face of new challenges and improving their security of access to land and resources. Already scaled up across pastoral areas in Ethiopia, the EU-funded Piloting of PRM project in Kenya and Tanzania, coordinated by the International Land Coalition and implemented by the Resource Conflict Institute, Tanzania Natural Resource Forum, ILRI and VSF-Belgium, provided the opportunity to test the innovation in new contexts.